Examining the Factors Influencing Applicants' Placement on One General Surgery Program's Rank Order List. Issue 5 (May 2023) - Hahn, Alexandra; Gorham, Jessica; Mohammed, Alaa; Strollo, Brian; Fuhrman, George
Purpose: Surgery residency applications include variables that determine an individual's rank on a program's match list. We performed this study to determine which residency application variables are the most impactful in creating our program's rank order list. Methods: We completed a retrospective examination of all interviewed applicants for the 2019 match. We recorded United States Medical Licensing Examinations (USMLE) step I and II scores, class quartile rank from the Medical Student Performance Evaluation (MSPE), Alpha Omega Alpha (AOA) membership, geographic region, surgery clerkship grade, and grades on other clerkships. The MSPE and letters of recommendation were reviewed by two of the authors and assigned a score of 1 to 3, where 1 was weak and 3 was strong. The same two authors reviewed the assessments from each applicant's interview and assigned a score from 1-5, where 1 was poor and 5 was excellent. Univariate analysis was performed, and the significant variables were used to construct an adjusted multivariate model with significance measured at P < .05. Results: Univariate analysis for all 92 interviewed applicants demonstrated that USMLE step 2 scores ( P = .002), class quartile rank ( P = .004), AOA status ( P = .014), geographic location ( P < .001), letters of recommendation ( P < .001), and interview rating ( P < .001) were significant in predicting an applicant's position on the rank list. On multivariate analysis only USMLE step 2 ( P = .018) and interview ( P < .001) remained significant. Conclusion: USMLE step 2 and an excellent interview were the most important factors in constructing our rank order list. Applicants with a demonstrated strong clinical fund of knowledge that develop a rapport with our faculty and residents receive the highest level of consideration for our program.